African American Literature Beyond Race : an Alternative Reader. - Jarrett, Gene Andrew, 1975- (NYU Press, 2006)
It is widely accepted that the canon of African American literature has racial realism at its core: African American protagonists, social settings, cultural symbols, and racial-political discourse. As a result, writings that are not preoccupied with race have long been invisible-unpublished, out of print, absent from libraries, rarely discussed among scholars, and omitted from anthologies. However, some of our most celebrated African American authors-from Zora Neale Hurston and Richard Wright to James Baldwin and Toni Morrison-have resisted this canonical rule, even at the cost of critical d.